Computational Algorithms Supporting the Bridge Management System - Lucjan Janas; Bartosz Miller; Adam Kaszyński (The Baltic Journal of Road and Bridge Engineering)
This paper presents a novel approach to the creation of a ranking list of bridges with the highest priority for repair, renovation or exchange. Two main aspects addressed herein are studied. First concerning parameters, which must be taken into account while creating the list of bridges with priority for repair or renovation. Second concerning proposition of algorithms for creating such list. A set of factors that affect this priority has been created; the three main ones were selected: technical condition factor, safety factor and the importance for the roads network factor. Three self-reliant algorithms of the ranking list creation are presented. One of them is the so-called “expert algorithm”, based on artificial neural networks – gives the best result and has been indicated as the recommended one. This algorithm, engaging back-propagation multilayer artificial neural network, is implemented in the General Directorate for National Roads and Motorways in Poland and is applied as a supporting tool in managing road-engineering structures.